-3n(8n-7)-6n=-219

Simple and best practice solution for -3n(8n-7)-6n=-219 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3n(8n-7)-6n=-219 equation:



-3n(8n-7)-6n=-219
We move all terms to the left:
-3n(8n-7)-6n-(-219)=0
We add all the numbers together, and all the variables
-6n-3n(8n-7)+219=0
We multiply parentheses
-24n^2-6n+21n+219=0
We add all the numbers together, and all the variables
-24n^2+15n+219=0
a = -24; b = 15; c = +219;
Δ = b2-4ac
Δ = 152-4·(-24)·219
Δ = 21249
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{21249}=\sqrt{9*2361}=\sqrt{9}*\sqrt{2361}=3\sqrt{2361}$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(15)-3\sqrt{2361}}{2*-24}=\frac{-15-3\sqrt{2361}}{-48} $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(15)+3\sqrt{2361}}{2*-24}=\frac{-15+3\sqrt{2361}}{-48} $

See similar equations:

| 34-6w10=23 | | d/8+d/10=240 | | 4x+27=-10x-33 | | 1+8v=2+8v | | 2(3r-4)-1=(r+2)-21 | | 12x-7x-3x+4=-8 | | x/10-1/5=30 | | Y=-150p+2200 | | -6(8x+4)-6x=-240 | | 12x-8=2x+10 | | 3.00+0.75x=54 | | 3(y+1)+4=2(y+1)+y+y | | 1/3x-15=0 | | 10/x+3=5/8 | | −2x+4=2x+4 | | x/4-18=5 | | 12.4-2.8x-8.4=-12.8 | | 8(4-6n)=-8(-1+7n) | | 8w+2w-7w+3w=24 | | 4/6=18/y | | 8x-28-2x=59 | | 20m−14m−4m−m−1=2 | | 3(2+5m)-10=-22+6m | | x+4x+8x=1300 | | -6k-3k=3+24 | | -3(3-2V)=6v-9 | | -60=-6(-5)v | | 9z+3-4z=9 | | 5m=-15-10 | | -26+44=-4w+2w | | -13(x-4)=-60 | | 158=10x+14-x |

Equations solver categories